Volume 5B: Pipeline and Riser Technology 2015
DOI: 10.1115/omae2015-41305
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a Post-Installable Deepwater Monitoring System Using Fiber-Optic Sensors

Abstract: This paper addresses the design and development of a fiber-optic monitoring system that can be deployed on existing deep water risers and flow lines; and provides a summary of test article fabrication and the subsequent laboratory testing performed at the National Aeronautics and Space Administration-Johnson Space Center (NASA-JSC). A major challenge of a post-installed instrumentation system is to ensure adequate coupling between the instruments and the riser or flow line of interest. This work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…(Left) Design of subsea pipeline clamp containing FBG sensors. 212 (Right) Photo of FBG clamp installed on a subsea pipeline. 213 …”
Section: Sensing Strategies For Subsea Pipeline Shmmentioning
confidence: 99%
“…(Left) Design of subsea pipeline clamp containing FBG sensors. 212 (Right) Photo of FBG clamp installed on a subsea pipeline. 213 …”
Section: Sensing Strategies For Subsea Pipeline Shmmentioning
confidence: 99%
“…Both classical and modern instruments are used for flood monitoring. Easily detects the leakage and defect Still in research process to apply for BCPs [32] Radiography Easily distinguishes deep layers of BCPs Can be the cause of damage for humans and sea animals [33] Fiber optics Precise results with less loss of data Installation is tedious, and permanent installation is required for it [34] From Table 8, it is observed that the output readings from classical instruments like acoustic emissions can be interrupted on irregular surface applications. Ground penetrating radar (GPR) and electrical field signature can provide moderate results with their continuous attachment to the observation units.…”
Section: Floodsmentioning
confidence: 99%
“…Further, external surface load such as traffic, heavy equipment, and superstructure built on the BCPs also impact its integrity [16][17][18][19][20][21][22][23][24][25]. Likewise, flood [26][27][28][29][30][31][32][33][34], blasting [35][36][37] and earthquakes [38][39][40][41][42][43][44] also affect the safe operations of BCPs.…”
Section: Introductionmentioning
confidence: 99%
“…The Clear Gulf JIP relies on oil and gas industry experts as well as test facilities at NASA. While the sensors on this project were dry-installed, the post-installed clamp design and adhesion to the pipe is recently improved with fundamental research and testing conducted by NASA Johnson Space Center [13,14] for long-term service life verification. The new clamp design is shown in Figure 12 with several enhancements over the prior clamp design [4,5].…”
Section: Long-term Development With Clear Gulf Jipmentioning
confidence: 99%